ANALISIS PENGAMBILAN KEPUTUSAN PEMBELIAN KREDIT DAN SEWA KENDARAAN ANGKUTAN PRODUKSI PADA PT. TANJUNG BUYU PERKASA PLANTATION DI BERAU - -, Muhammad Yusuf (EKONOMIA, 2018)
Â The purpose of this study is to determine whether the decision of the company to purchase vehicle transportation loan production more profitable compared with the operating lease, both in the short and long term.The theory used is Management Accounting, Cost Accounting, Credit Interest and Leasing.Analyzer using NPV and Differential Cost by comparing two variables that is credit purchase and rent use,The NPV analysis for 3 years shows that the total cost of Credit Purchase is IDR 768,722,865,- while operating leaseÂ is IDR 943.071.490,- so that Credit Purchase more profitable equal to IDR 174.348.625,-. Analysis Short-term cash flow (1 year) also shows that in the 1st year for Credit Cash Purchase of IDR 350,606,965,- while the cash flow Operating Lease amounted to IDR 367.821.888,- so that Credit Purchases remained more profitable of IDR 17.214.923,-. Result of research indicate that Purchase Credit of production transportation at PT. Tanjung Buyu Perkasa Plantation in Berau is more profitable compared to operating lease.